International survey of people living with chronic conditions: development and evaluation of the PaRIS Patient Questionnaire (PaRIS-PQ) in 18 countries - Valderas, Jose M; Porter, Ian; Evans, Jonathan P; Heijmans, Monique; Rijken, Mieke; Groene, Oliver; Bloemeke-Cammin, Janika; Sunol, Rosa; Williams, Rachel; Ballester, Marta; de Bienassis, Katherine; Kendir, Candan; et al. (BMJ quality & safety, 2025)
The Patient Reported Indicator Surveys (PaRIS) initiative of the Organisation for Economic Co-operation and Development aimed to develop a valid and reliable instrument for self-reported assessment of health outcomes and experiences in primary and ambulatory care for people living with chronic conditions. This paper reports on the development and evaluation of the PaRIS Patient Questionnaire (PaRIS-PQ) in an 18-country field trial. Following systematic reviews of instruments measuring core domains in the PaRIS conceptual framework (outcomes, experiences, health and healthcare capabilities and health behaviours), four instruments for each domain were shortlisted, and their psychometric performance was assessed using the Evaluating the Measurement of Patient-Reported Outcomes tool. In a modified Delphi procedure, one instrument was selected for each domain, along with additional relevant items. The preliminary English questionnaire was translated and cognitively tested. Psychometric evaluation was conducted on field trial data at item (missingness, distribution, ceiling/floor effects) and scale level (reliability, structure, construct validity). 217 instruments were identified measuring one or more of the domains of the conceptual framework. Following mapping and prioritisation, the first draft of the PaRIS-PQ included 118 items. In the field trial (18 countries, 10 894 patients) median completion time ranged 24-33 minutes. PaRIS-PQ performed well at item and scale level. Reliability was ≥0.70 for most relevant measures at patient level, but not at practice and country level. Validity was adequate overall. Removal of additional items (3) resulted in the final PaRIS-PQ (115 items). PaRIS-PQ demonstrates adequate psychometric performance for measuring experiences and outcomes of primary care for people living with chronic conditions. The instrument facilitates the collection of essential information for health policy and systems decision-making.